1994
DOI: 10.1002/smj.4250150305
|View full text |Cite
|
Sign up to set email alerts
|

The effects of board size and diversity on strategic change

Abstract: This study examines an important potential conflict between the institutional, governance, and strategic functions of boards. We specifically test how higher levels of board size and diversity, traditionally associated with optimal institutional and governance performance of boards, affect the boards ability to initiate strategic changes during periods of environmental turbulence. Our findings suggest that board diversity, in particular, may be a significant constraint on strategic change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
698
5
25

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 986 publications
(757 citation statements)
references
References 33 publications
29
698
5
25
Order By: Relevance
“…2 We further added board controls, at firm level, that could affect board group dynamics and subsequent decisions made over environmental practices. We controlled for board size because larger boards tend to have more network ties (Goodstein, Gautam, & Boeker, 1994) and be less effective at decision making and monitoring (Dalton, Daily, Johnson, & Ellstrand, 1999;Judge & Zeithaml, 1992). We also accounted for CEO duality because such powerful CEOs potentially influence board decisions, although this was not found to be relevant to environmental practices in prior studies (Berrone & Gomez-Mejia, 2009;McKendall et al, 1999;Post, Rahman, & Rubow, 2011).…”
Section: Independent Variablesmentioning
confidence: 99%
“…2 We further added board controls, at firm level, that could affect board group dynamics and subsequent decisions made over environmental practices. We controlled for board size because larger boards tend to have more network ties (Goodstein, Gautam, & Boeker, 1994) and be less effective at decision making and monitoring (Dalton, Daily, Johnson, & Ellstrand, 1999;Judge & Zeithaml, 1992). We also accounted for CEO duality because such powerful CEOs potentially influence board decisions, although this was not found to be relevant to environmental practices in prior studies (Berrone & Gomez-Mejia, 2009;McKendall et al, 1999;Post, Rahman, & Rubow, 2011).…”
Section: Independent Variablesmentioning
confidence: 99%
“…11; larger the size of the board, the more competent the corporate governance will be owing to the large pool of skills, knowledge and expertise. In addition, bigger boards are more capable of offering diverse assistance to the firm in light of securing resources and decreasing environmental risks (Goodstein et al, 1994;Nazli Anum, 2010;Pearce & Zahra, 1992;Pfeffer, 1987).…”
Section: The Executive Committee Size and Firm Performancementioning
confidence: 99%
“…In sum, common arguments contend that larger board are more diverse and have significant associations to the external environment to assist the firm in obtaining critical resources and ideas for decisions pertaining to corporate policies that are known to improve efficiency (Goodstein et al, 1994; Nanka-Bruce, 2011). Chaganti et al (1985) and Dalton et al (1998), revealed that large boards are significant for the experiences contributed by the members to the board discussions and decision making.…”
Section: The Executive Committee Size and Firm Performancementioning
confidence: 99%
“…Although the most important role of the directors is to monitor managers to mitigate agency conflicts between managers and shareholders (Fama & Jesen, 1983), they also provide resources including expertise, advice, and guidance so that the organization can make better strategic choices (Boyd, 1990;Daily & Dalton, 1994;Goodstein, Gautam, & Boeker, 1994;Pfeffer & Salancik, 1978;Shropshire, 2010). The advice, information, and guidance available through the directors can at least partially influence strategic decisions of an organization (Westphal & Fredrickson, 2001).…”
Section: Board Of Directors As An Integration Mechanismmentioning
confidence: 99%